2004
DOI: 10.1255/ejms.661
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Identification of Cyclic Polysulfides in Sediment of the Eastern Gulf of Finland. I

Abstract: Structures of six cyclic polysulfides, previously unkown as organic environmental pollutants, were analyzed from a sediment sample from the Eastern Gulf of Finland. The determinations were done by gas chromatography (GC) coupled to mass spectrometry. High-resolution mass spectrometry measurements of the isotopic composition of four compounds could be done to confirm their molecular formulae. Total low-resolution mass spectrometry spectra were used to elucidate structures of all six compounds by a thermochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Similar reasons determine complex multi-vector geochemical investigations of bottom sediments and mud volcanoes on the shelf and on the deepocean floor of Taiwan, Brunei and Malaysia (Chen et al, 2014). Similar studies of deep-sea sediments and their inherent organic compounds as prerequisites for oil-and-gas subsurface potential have been conducted in the Gulf of Finland for a long time (Khoroshko et al, 2004).…”
Section: Study Areamentioning
confidence: 70%
See 1 more Smart Citation
“…Similar reasons determine complex multi-vector geochemical investigations of bottom sediments and mud volcanoes on the shelf and on the deepocean floor of Taiwan, Brunei and Malaysia (Chen et al, 2014). Similar studies of deep-sea sediments and their inherent organic compounds as prerequisites for oil-and-gas subsurface potential have been conducted in the Gulf of Finland for a long time (Khoroshko et al, 2004).…”
Section: Study Areamentioning
confidence: 70%
“…Near-surface exploration methods have been used with mixed success in petroleum exploration, which has led to discussions about the complex nature of hydrocarbon leakage in marine conditions. Numerous thematic studies have demonstrated the effectiveness of near-surface geochemical exploration methods (Villinski et al, 2000;Khoroshko et al, 2004;Gay et al, 2011;Kallmeyer et al, 2012;Mirza et al, 2012;Aeppli et al, 2014). However, additional studies are required to specify conditions of applicability of geochemical methods and to understand when these methods work, what effect the choice of equipment and analytical procedures has, what best suits a specific parameter of the marine system, and, most importantly, how to interpret the results properly.…”
mentioning
confidence: 99%
“…Special works on detection and structure determination of various polysulfides as environmental organic pollutants from sediment samples from the Eastern Gulf of Finland have been accomplished in Saint-Petersburg Center of Ecological Safety Russian Academy of Sciences (St Petersburg). [221][222][223] In these studies, a combination of GC with low-and high-resolution mass spectrometry were employed.…”
Section: Environmentalmentioning
confidence: 99%